The Reported Speech Act in Maccan Surah - Khorsheed Mama, Nizar; Muhammed Nuree, Abdul azeez Hassan (Journal of Duhok University, 2019)
There is no disagreement that pragmatics is one of the most important modern linguistics trends and the most diverse and comprehensive, and as the multiplicity of premises and the differences in the study of pragmatics have great impact on the making of some kind of overlap with other linguistics fields, and the theory of speech act is considered as the most important trends of pragmatic. In this sense, the meaning of speech act is to perform action by means of speech, i.e., speech is the actor and the main reason for the recipient to do something and cease it. And this is what has put this theory in the prospects of contextual frames. And led to the division of the discourses indicatively on its partial units to know its psychological, social and cultural conditions. And perhaps the most important distinguished feature of Arabic pragmatics is the study of ancient Arab linguists of the sentences in two different trends or directions: grammatically which views speech as an informing or a telling, and rhetorical indicative pragmatics that depends on the precise intent of the speaker, which they called in their sources by matching the speech to the appropriate situation and its departure from the outward obligation. Therefore, for them, it comes out for many purposes and aims. Among these purposes, we will choose “reported” which we will discuss in Maccan Surah, due to the variety of methods of expression and the emergence of this purpose specifically more than other Surah, because the stylistic nature of these Surah. “the reported speech act in Maccan surah” are characterized by many characterizations such as preaching, advising, guidance and emphasis on important issues especially those related to “faith”, and the oneness of Allah. i.e., the “Approbation” that Allah - the Almighty – is the creator, the living provider, mastermind of all being as well as the oneness of Allah. That is praying and obedience should only be for Allah and avoid polytheism. Through the analysis of selected examples from holy Quran verses according to pragmatic methods, we discovered many semantic secrets contained in these verses.